Antioxidant activity of spearmint (Mentha spicata L.) leaves extracts by supercritical carbon dioxide (SC-CO2) extraction - Bimakr, Mandana; Abdul Rahman, Russly; Ganjloo, Ali; Taip, Farah Saleena (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
In this study, the effects of pressure (100–300 bar), temperature (40–60ºC) and co-solvent flow rate (3–9 g/min) on antioxidant activities of supercritical carbon dioxide (SC-CO²) extracts of spearmint leaves were determined using full factorial in the frame of complete randomize design (CRD). The antioxidant activity of SC-CO² extracts was determined by DPPH radical scavenging method. The results showed that extraction pressure, temperature and co-solvent flow rate had significant effect (P < 0.05) on antioxidant activity of extracts obtained. The highest antioxidant activity (71.00 ± 2.65%) was obtained at 200 bar pressure, 50ºC and 6 g/min co-solvent flow rate. However, all of the extracts obtained in this study had significantly higher antiradical activities varying from 35.62 ± 0.34% to 72 ± 3.17% compared to butylated hydroxytoluene (BHT) as a reference. These results indicated that supercritical carbon dioxide is a promising alternative process for recovering compounds of high antioxidant activities from spearmint leaves.